Respuesta :

Answer:

[tex]\sum_{i}^{4}2(3)^{i-1}<\sum_{i}^{5}3(2)^{i-1}<\sum_{i}^{7}(2)^{i-1}<\sum_{i}^{5}(3)^{i-1}[/tex].

Step-by-step explanation:

The sum of finite geometric series is given as:

[tex]S_{n}=\sum_{i}^{n}a_{i}r^{i-1}=a_{1}(\frac{1-r^n}{1-r})[/tex]

Now, [tex]\sum_{i}^{4}2(3)^{i-1}[/tex] can be solved as:

[tex]\sum_{i}^{4}2(3)^{i-1}=2(\frac{1-3^4}{1-3})=2(\frac{1-81}{-2})=80[/tex]

Also, [tex]\sum_{i}^{5}3(2)^{i-1}[/tex] can be solved as:

[tex]\sum_{i}^{5}3(2)^{i-1}=3(\frac{1-2^5}{1-2})=3(\frac{1-32}{-1})=93[/tex]

Also, [tex]\sum_{i}^{7}(2)^{i-1}[/tex]can be solved as:

[tex]\sum_{i}^{7}(2)^{i-1}=\frac{1-2^7}{1-2}=\frac{1-128}{-1}=127[/tex]

and [tex]\sum_{i}^{5}(3)^{i-1}[/tex] can be solved as:

[tex]\sum_{i}^{5}(3)^{i-1}=\frac{1-3^7}{1-3}=\frac{1-2187}{-2}=1093[/tex]

We can observe that [tex]80<93<127<1093[/tex], thus

[tex]\sum_{i}^{4}2(3)^{i-1}<\sum_{i}^{5}3(2)^{i-1}<\sum_{i}^{7}(2)^{i-1}<\sum_{i}^{5}(3)^{i-1}[/tex].

Answer:

The above answer is wrong. The last two boxes should be switched.

ACCESS MORE